PUBLIC DOMAIN AS INDONESIA'S TRADEMARK LAW IN THE UTILITARIAN'S PERSPECTIVE - Trisa Rembonita; Fokky Fuad Wasitaatmaja (Asosiasi Dosen Muda Indonesia, 2024)
Indonesia’s Intellectual property rights encompass trademarks’ protection, copyrights, patents, geographical indications, industrial designs, circuit layout designs, and trade secrets, including aqua, the botol, and ecoprint, which use generic words and non-distinctiveness and disturb public order. Ecoprint became a public domain in 2001. However, it was approved as a trademark of products by the DGIPR in 2019 and protected by the law, allowing it to reap the economic benefits. The research problem is: How is the public domain of ecoprint used by trademarks being reviewed in positive Indonesian law from the perspective of utilitarian theory? The research uses a normative descriptive method with a conceptual approach and a comparative approach from secondary data, primary and secondary legal materials, and is analyzed using Jeremy Bentham's theory of utility,